A novel splicing mutation in 5'UTR of GJB1 causes X‐linked Charcot—Marie–tooth disease. Issue 3 (17th November 2022) - Li, MeiYi; Yin, Minna; Yang, Li; Chen, Zhiheng; Du, Peng; Sun, Ling; Chen, Juan
Abstract: Background: Charcot–Marie–Tooth (CMT) disease is the most frequent hereditary motor sensory neurological disease. GJB1 gene is the second most frequent cause of CMT, accounting for approximately 10% of CMT cases worldwide. We identified a large Han family with X‐linked CMT disease. Methods: In this study, the probands and his mother underwent electrophysiological examinations and other family members were assessed retrospectively. Whole‐exome sequencing, Sanger sequencing, and SNP array linkage analysis were performed to find and confirm the variant. The functional effect of the identified variant was further investigated in HEK293 cells and MCF‐7 cells by minigene splicing assay. Results: The affected individuals had some clinical symptoms including symmetric atrophy and progressive weakness of the distal muscles in their twenties. Electrophysiological examinations result in peripheral nerve injury of the upper and lower limbs. Whole‐exome sequencing identified a novel hemizygous deletion mutation (NM_000166: c.‐16‐8_‐14del) in the GJB1 gene. SNP array linkage analysis and co‐segregation analysis confirmed this mutation. Minigene splicing assay verified that this mutation leads to the activation of cryptic splicing sites in exon 2 which results in the deletion of exon 2. Conclusion: Our study provides theoretical guidance for prenatal diagnosis and subsequent fertility of this family. This result expands the spectrum of mutations in GJB1 known to be associated with CMTX and contributes to the diagnosis of CMT and clinical genetic counseling. Abstract : We identified a novel mutation (Uncertain Significance pathogenicity class) in GJB1 by whole exome sequencing in a large Chinese Han family with CMT disease when the proband came for genetic counseling. By NGS‐based SNP haplotyping and Minigene Splicing Assay, we finally upgraded the pathogenicity class from class 3 (Uncertain Significance) to class 5 (pathogenic) and provides theoretical guidance for prenatal diagnosis and subsequent fertility of this family.